2011
DOI: 10.1016/j.renene.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Solar cooling for small office buildings: Comparison of solar thermal and photovoltaic options for two different European climates

Abstract: We present a comparison of solar thermal and solar electric cooling for a typical small office building exposed to two different European climates (Freiburg and Madrid). The investigation is based on load series for heating and cooling obtained previously from annual building simulations in TRNSYS. A conventional compression chiller is used as the reference system against which the solar options are evaluated with respect to primary energy savings and additional cost. A parametric study on collector and storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 14 publications
0
31
0
Order By: Relevance
“…These research results have also indicated that based on Energies 2017, 10, 1463 4 of 27 different solar cooling technologies and different climates, the energy savings could be 25% to 90% compared with the traditional HVAC system. In addition, there are also a number of comparative studies on the performances within various solar cooling systems, which include the comparison of solar absorption cooling with solar electric cooling [37][38][39][40], solar desiccant cooling with solar absorption cooling [41], and hybrid solar desiccant cooling with other solar cooling systems [42][43][44][45]. Gagliano et al [46] reported that the hybrid solar desiccant integrated vapour compression cooling system could achieve 40% primary energy savings compared to the solar absorption cooling, and 150% savings respect to the conventional vapour compression cooling system.…”
Section: Solar Air Conditioning Technology Reviewmentioning
confidence: 99%
“…These research results have also indicated that based on Energies 2017, 10, 1463 4 of 27 different solar cooling technologies and different climates, the energy savings could be 25% to 90% compared with the traditional HVAC system. In addition, there are also a number of comparative studies on the performances within various solar cooling systems, which include the comparison of solar absorption cooling with solar electric cooling [37][38][39][40], solar desiccant cooling with solar absorption cooling [41], and hybrid solar desiccant cooling with other solar cooling systems [42][43][44][45]. Gagliano et al [46] reported that the hybrid solar desiccant integrated vapour compression cooling system could achieve 40% primary energy savings compared to the solar absorption cooling, and 150% savings respect to the conventional vapour compression cooling system.…”
Section: Solar Air Conditioning Technology Reviewmentioning
confidence: 99%
“…A comparison between solar thermal and solar electric cooling systems for a typical small office building in two different European locations (Freiburg, Germany and Madrid, Spain) by means of TRNSYS was performed by Hartmann et al [13]. The authors investigate, varying solar collecting area, the performance of the systems on the basis of energy and economic indices.…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [15] the authors compare by means of TRNSYS the performance of solar heating and cooling systems based, respectively, on solar thermal collectors and PV panels used to satisfy energy demand of a small office building in two different European climates (Freiburg/Germany and Madrid/Spain). Varying solar collecting area the authors analyze through energy and economic indices the performance of the systems.…”
Section: Introductionmentioning
confidence: 99%